2020
DOI: 10.1186/s12955-020-01381-5
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among children with transfusion-dependent thalassemia: A cross-sectional study in Malaysia

Abstract: Background: The treatment of children with transfusion-dependent thalassemia (TDT) in Malaysia has progressed since 2005. This study provides an updated health-related quality of life (HRQoL) assessment for children with the disorder and the factors affecting the HRQoL. Methods: A cross-sectional HRQoL survey of Malaysian children with TDT was conducted using the PedsQL™ 4.0 Generic Core Scales. Patients with non-transfusion dependent thalassemia and other haemoglobinopathies were excluded. Parent-proxy and se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
3
14
0
Order By: Relevance
“…Understanding how the disease and treatment affects the HRQoL dimensions is imperative in improving the delivery of care beyond the clinical markers of the disease. 4 It is in line with the results of a study conducted by Behdani et al (2015) using the PSCL questionnaire showed that there was a significant relationship between depression, anxiety, quality of life, and behavioral screening between thalassemia major adolescents and healthy adolescents. Patients with thalassemia have a lower QOL than their peers (P = 0.001), the rate of depression is higher in this group (P = 0.015), Also behavioral problems in these children are more than healthy subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Understanding how the disease and treatment affects the HRQoL dimensions is imperative in improving the delivery of care beyond the clinical markers of the disease. 4 It is in line with the results of a study conducted by Behdani et al (2015) using the PSCL questionnaire showed that there was a significant relationship between depression, anxiety, quality of life, and behavioral screening between thalassemia major adolescents and healthy adolescents. Patients with thalassemia have a lower QOL than their peers (P = 0.001), the rate of depression is higher in this group (P = 0.015), Also behavioral problems in these children are more than healthy subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Higher pretransfusion hemoglobin levels and low serum ferritin levels were independent predictors of better QoL scores (Elalfy et al, 2014;Mevada et al, 2016), while poor QoL was associated with the presence of complications, low economic level, female sex, hepatomegaly, high ferritin level (Clarke et al, 2010;Hakeem et al, 2018;Jameel & Im, 2015;Sobota et al, 2011;Tuysuz & Tayfun, 2017), increasing age, and the use of combined therapy of ICT, (Shafie et al, 2020). Furthermore, delays in diagnosis and introduction of ICT contributed to a negative effect on the total PedsQL score (Mevada et al, 2016).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Children with TDT had significantly lower school functioning compared to healthy children (Mevada et al, 2016;Nashwan et al, 2018). Using deferoxamine was a predictor for lower school functioning (Thavorncharoensap et al, 2010), while the physical functioning of TDT patients was predicted by the patient's age (Shafie et al, 2020), severity of the disease , history of thalassemia in the family, and low financial status (Ayoub et al, 2013).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Physical health Education (higher) 5.17 Our findings suggested that the participants most likely could have received adequate and appropriate medical treatment early in life because the majority have no other co-morbidities, have gained employment and have completed at least secondary education. Such achievements would be their main concerns and struggles in life seven to ten years ago [4,26]. The ability to obtain higher educational level has also been used as a benchmark towards a higher social level, better QOL and a better income [25][26][27][28].…”
Section: Multiple Linear Regression a (Coefficient (95% Ci))mentioning
confidence: 99%